DAMPAK PEMBANGUNAN OBYEK WISATA TERHADAP TINGKAT PENDAPATAN PENDUDUK LOKAL (STUDI KASUS WISATA DESA DARAMISTA SUMENEP) - Sayyidi; Lilis Kurniawati (STIE Bakti Bangsa Pamekasan, 2020)
The existence of a tourist attraction can not be separated from the local economic development that is increasing economic activity within the area, include the upgrading of tourist attraction. The existence of Bukit Tinggi object has a lot contribution to the regional economy. Economic development arising from the Bukit Tinggi object can encourage the creation of employment opportunities and enhancing the community's economy around. So it could trigger a regional sustainable development. The purpose of this study was to determine the impact of expansion on the Bukit Tinggi object of local economic development in Sumenep regency. To determine the focus of this study, the researchers formulated the problem as that is How the impact of expansion on the Bukit Tinggi object of local economic development and government's role in the expansion of tourism on local economic development. The focus in this research the impact of expansion on the Bukit Tinggi object of local economic development in Blitar regency. Data collection methods used in this study is the method of observation, depth interviews and documentation